2015
DOI: 10.1371/journal.pone.0120283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Vitro Syncytium Formation on the Severity of Human Metapneumovirus Disease in a Murine Model

Abstract: Human metapneumovirus (HMPV) is an important cause of acute respiratory tract infections (ARTI) in children, elderly individuals and immunocompromised patients. In vitro, different HMPV strains can induce variable cytopathic effects ranging from large multinucleated syncytia to focal cell rounding. In this study, we investigated the impact of different in vitro phenotypes of two HMPV strains on viral replication and disease severity in a BALB/c mouse model. We first generated two recombinant GFP-expressing HMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 40 publications
(56 reference statements)
10
31
0
Order By: Relevance
“…Interestingly, our findings corroborates with a previous report that demonstrated the differences in replication fitness between HMPV genotypes in vitro and in vivo [47]. The study by Aerts et al showed that HMPV genotype A replicates to a significantly higher titers than genotype B in LLC-MK2 cells and in the lungs of BALB/c mice on day 4 post-infection, but the viral titers of genotype A decreased more rapidly than genotype B after day 4 [47]. As observed in other viral genotypes/serotypes [48,49], the differences in replication capacity may contribute to the competitive, transmission and epidemiological fitness differences between HMPV genotypes [50], which in turn may dictate the spread and evolution of both genotypes in the human population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, our findings corroborates with a previous report that demonstrated the differences in replication fitness between HMPV genotypes in vitro and in vivo [47]. The study by Aerts et al showed that HMPV genotype A replicates to a significantly higher titers than genotype B in LLC-MK2 cells and in the lungs of BALB/c mice on day 4 post-infection, but the viral titers of genotype A decreased more rapidly than genotype B after day 4 [47]. As observed in other viral genotypes/serotypes [48,49], the differences in replication capacity may contribute to the competitive, transmission and epidemiological fitness differences between HMPV genotypes [50], which in turn may dictate the spread and evolution of both genotypes in the human population.…”
Section: Discussionsupporting
confidence: 93%
“…However, the viral load of genotype A-infected patients who enrolled ≥6 days were observed to be significantly lower compared those who enrolled 3-5 days after symptom onset, due to the fact they enrolled much later during the course of infection, in which most viruses would have been cleared by immunity. Interestingly, our findings corroborates with a previous report that demonstrated the differences in replication fitness between HMPV genotypes in vitro and in vivo [47]. The study by Aerts et al showed that HMPV genotype A replicates to a significantly higher titers than genotype B in LLC-MK2 cells and in the lungs of BALB/c mice on day 4 post-infection, but the viral titers of genotype A decreased more rapidly than genotype B after day 4 [47].…”
Section: Discussionsupporting
confidence: 92%
“…pSP72 plasmids (Promega) encoding the full-length genomic cDNA of HMPV B2/CAN98-75 or A1/C-85473 strains (GenBank accession numbers: AY145289.1 and KM408076.1, respectively) were constructed as previously described [29, 34]. To generate G- or SH-deleted viruses, plasmids encoding HMPV antigenomes were amplified with Phusion DNA polymerase (New England Biolabs) using primers (listed in Table 1) designed to match with the 3’ and 5’ regions of either G or SH genes, and taking care to conserve an intergenic sequence between flanking genes (as represented in Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
“…BSR-T7 cells were transfected with the HMPV antigenome constructions plus 4 supporting plasmids, encoding N, P, L, and M2-1 ORFs of CAN98-75 and LLC-MK2 cells were added for co-culture (2 to 3 days), as previously described [29]. Cells were harvested, sonicated, centrifuged and the supernatant was diluted to inoculate LLC-MK2 monolayers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation